Pengaruh Aplikasi Pupuk Organik dan Pestisida Organik terhadap Produktivitas Terung (Solanum melongena) dan Tingkat Bahaya Erosi - Idah Andriyani; Fiona Cahya Patricia (The University of Lampung, 2021)
This study aims to analyze the effects of the use of organic fertilizers and organic pesticides on eggplant productivity and the level of erosion hazards that occur on these intensive agricultural lands. The use of organic fertilizers and pesticides is expected to improve soil quality which in turn will increase crop productivity and reduce erosion yield. Randomized block design (RBD) was used with a combination of dosage treatment of organic fertilizers (P) and organic pesticides (B). The dosages of organic fertilizers used were: 0 kg/bed (P1/control), 1 kg/bed (P2), 1.5 kg/bed (P3) and 2 kg/bed (P4). The doses of pesticides used were chemical pesticides 2 ml/liter (B1/control), organic pesticides 7 ml/liter (B2), 9 ml/liter (B3) and 11 ml/liter (B4). The highest productivity research results were obtained from combination of P4B1 (fertilizer dose 2kg/bed + chemical pesticides). This shows that organic fertilizers and pesticides can increase plant productivity. However, organic pesticides have not been able to reduce pest attacks during the fertilization phase. On the other hand, the rate of erosion has actually increased which is not significantly different between the use of organic fertilizers and chemical fertilizers. This is due to the increase in the content of organic matter and changes in soil texture which cause the soil to become loose and crumb so that it is more easily eroded. Thus the use of organic fertilizers and pesticides can be used continuously in intensive agriculture but must be accompanied by other conservation activities to reduce the erosion yield. In addition, it is necessary to develop more effective organic pesticides to eradicate pests and plant diseases. Keywords: erosion, eggplant plants, intensive agriculture, organic fertilizer, organic pesticide.